Masticatory performance in patients with jaw muscle pain: A case–control study - Al Sayegh, Samaa; Christidis, Nikolaos; Kumar, Abhishek; Svensson, Peter; Grigoriadis, Anastasios (Frontiers in Dental Medicine, 2022)
Introduction Masticatory function is often impaired in patients with painful temporomandibular disorders (TMD); therefore, more detailed studies on comminution and mixing ability are warranted in well-defined TMD patients with chronic myalgia. Moreover, there is a need to explore the correlation between any changes in perceived pain or fatigue in such patients and the masticatory function. Materials and methods Self-assessments using questionnaires regarding pain, oral health, jaw function, masticatory ability, fear of movement, and psychosocial signs were answered by all the participants. A series of chewing tasks involving viscoelastic food and two-colored gum were performed. Optical imaging and analysis were conducted. Bite force as well as characteristics of pain and fatigue were assessed. Results In patients, the fragmented soft candy particles were less in number and had larger median of area and minimum Feret's diameter after standardized chewing compared to healthy individuals (P = 0.02). Surprisingly, the two-colored Hue-Check gum was less mixed by the healthy controls since they displayed a greater variance of the hue (P = 0.04). There were significant differences between the patients and the healthy controls in the self-assessed masticatory ability, mainly regarding pain-related variables. Conclusions Objectively, TMD patients with chronic myalgia exhibited an impaired masticatory performance with less efficiency in comminuting soft viscoelastic food compared to the pain-free healthy control group. There was an agreement between the patients' self-assessed masticatory ability and the efficiency of their masticatory function.